THE REGULATORY MODEL FOR ERADICATION CORRUPTION IN INFRASTRUCTURE FUNDING - Fitriyaningrum, Julyatika; Arifin, Ridwan (Fakultas Hukum Universitas Muhammadiyah Magelang, 2019)
This study aims to identify the causes and formulate a regulatory model for the eradication of Corruption in regional infrastructure development funds in Indonesia. This research was conducted by examining cases and laws related to Corruption. Some of the causes of corruption in regional development funds are: 1)Historical Factors; 2)Economic Factors; 3)Cultural Factors and 4)Institutional Factors. Although all four factors have been identified, there are still many countries that have not succeeded in eradicating corruption. An extraordinary crime requires extraordinary effort. The Government of Indonesia needs to formulate legislative policies with those manifested in specific deviant provisions. In addition, there are four approaches that are needed, namely legal approach, moralistic-religious approach, socio-cultural approach, and educational approaches. Massive actions must also be taken in various regions to start an anti-corruption measure.